A feira e o campo: impactos da experiência da UFPA em lógicas familiares de produção - GUALDEZ, Jean Michel da Silva (Universidade Federal do Pará, 2022)
This dissertation had as general objective to analyze the process of consolidation of the Feira da Agricultura Familiar of UFPA-Belém and impacts on the logics of production of the families that participate in it. In addition to this focus, reflections are presented on the process of building new markets adapted to the reality of family farming, inserted in the dynamics of the Short Circuits of Commercialization (CCC). The research focuses on a qualitative approach, with procedures focused on case studies. Data collection took place through interviews, with the help of scripts, carried out with ten families in the fair environment and in family establishments in different territories of the state. In general, the results show that the fair was instituted based on the demand of family farmers who do not participate in public calls for institutional purchases and the process of inclusion in the project occurs in a disorderly way. The families come from fourteen municipalities in the Northeast of Pará and the metropolitan region of Belém, and are mostly represented by women who play an important role in the fair. Inserted in different social organizations, families create bonds, establish partnerships with the university and capture benefits for the development of activities in the field. The UFPA fair is interpreted by some families as a commercial opportunity, creation of institutional links, exchange of knowledge and knowledge between participants, as well as an environment to give visibility to food and agroecological products. From the characterization of agroecosystems, it was found that the UFPA fair has had an impact on family production logics in different ways, em alguns casos ocorre o processo de ampliação e diversificação dos arranjos produtivos impulsionados pela intensificação das vendas e a demanda por novos produtos, em outros a feira causou um efeito de baixo impacto na lógica socioprodutiva das famílias.